FRONT OFFICER & HOUSEKEEPER AS AGENCY IN PROMOTING CLEAN-LINESS OF THE MARINE ENVIRONMENT; AN ACTION RESEARCH FOR HOSPITALITY EDUCATION CURRICULUM - Andi Ade Zulkifli; Abdul Hafez Assad; Risman Jaya (Politeknik Pariwisata Makassar, 2025)
Although the marine environment is not a human habitat, it is utilised for two purposes: economically, to fulfil food needs based on marine biota, and for tourism, where recreational activities are carried out. This means that the issue of marine environmental cleanliness is highly significant and crucial. With regard to recreational needs, we believe that front office staff and housekeepers play a major role in promoting marine environmental cleanliness, especially in meeting recreational needs, where the presence of rubbish or dirt is difficult to avoid, while cleanliness is a major factor in meeting recreational needs. Through an action research approach, we constructed a learning model that we hope can be incorporated into the hospitality education curriculum in order to promote marine environmental cleanliness. The participation of lecturers and students in the field of hospitality in conducting action research, the construction of knowledge about learning models where enculturation is related to the culture of cleanliness, and support for understanding the function of the marine environment and the impact of its damage, especially in Indonesia, are the main topics with the aim of shaping the role of front officers and housekeepers in promoting marine environmental cleanliness. The results of this study show that the formation of a culture of cleanliness occurs through an understanding of the concepts of dirt and cleanliness based on general views or understanding, which are therefore not based on personal judgement or understanding, and can thus be practised and accepted in a general context. This understanding is formed through enculturation that takes place in formal vocational education, where understanding of the function of and impact of damage to the marine environment is taught as a form of cognitive support, with the aim of realising a culture of cleanliness. The understanding that sustainability as a concept can only be realised through the active role of humans as actors in life leads us to view the significance of this study in the formation of a formal vocational education curriculum in the hospitality field. Therefore, we hope that the results of this study can be developed for the purpose of forming an action-based curriculum for front officers and housekeepers as agents in promoting marine environmental cleanliness.